Functionality of streetscape. Example of Purvciems neighbourhood - Vugule, Kristīne; Rozenblate, Elīna (Landscape Architecture and Art, 2024)
Streets form the city’s living environment and play an important role in social interaction, they are the most accessible public outdoor spaces in the city. Many cities still prioritize vehicular traffic and it is necessary to improve streetscapes to make them more liveable, suitable, and inviting for pedestrians and cyclists. The paper presents research on streetscape analyses and development and highlights the streetscape as an essential part of the human living environment. Purvciems neighborhood in Riga is chosen as a pilot territory. Contemporary street planning approaches and tools are compared. Riga’s development planning documents are evaluated by assessing the development opportunities of the Purvciems neighborhood. The existing spatial structure and the ecological, economic, and social aspects of the street landscape of Purvciems are examined in detail. A development vision has been created to improve the functionality of the street landscape spaces in Purvciems at various scales, along with adaptable modular solutions. The developed recommendations and principles, adapted to specific locations, can be used for planning street landscapes in other neighborhoods of Riga and similar-scale territory planning.